2019
DOI: 10.1093/heapol/czz145
|View full text |Cite
|
Sign up to set email alerts
|

A path dependence analysis of hospital dominance in China (1949–2018): lessons for primary care strengthening

Abstract: Although China’s community health system helped inspire the 1978 Alma Ata Declaration on Health for All, it currently faces the challenge of strengthening primary care in response to hospital sector dominance. As the world reaffirms its commitment towards primary health services, China’s recent history provides a salient case study of the issues at stake in optimizing the balance of care. In this study, we have used path dependence analysis to explain China’s coevolution of hospital and primary care facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Numerous studies have demonstrated that satisfaction with compensation and job satisfaction are significant factors that affect the professional loyalty of primary healthcare workers [ 23 , 24 ]. China’s healthcare system remains predominantly centered around large hospitals [ 25 , 26 ] with primary healthcare institutions receiving comparatively less emphasis. Hence, the salaries offered by primary healthcare institutions are often insufficient to satisfy primary healthcare personnel, who may opt for non-primary healthcare institutions in pursuit of higher wages.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that satisfaction with compensation and job satisfaction are significant factors that affect the professional loyalty of primary healthcare workers [ 23 , 24 ]. China’s healthcare system remains predominantly centered around large hospitals [ 25 , 26 ] with primary healthcare institutions receiving comparatively less emphasis. Hence, the salaries offered by primary healthcare institutions are often insufficient to satisfy primary healthcare personnel, who may opt for non-primary healthcare institutions in pursuit of higher wages.…”
Section: Discussionmentioning
confidence: 99%
“…, 2019 ). Although China pioneered the ‘barefoot doctor programme’ in the 1960s to expand the coverage of primary care services in rural areas, this programme was unsuccessful in substantially changing the hospital domination of the health system due to scarce funds and unskilled workforces ( Zhang and Unschuld, 2008 ; Xu et al. , 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“… 11 In addition, due to the inferior QoC in lower-level medical institutes, patients tend to choose hospitals for medical assistance and bypass primary care institutes. 12 13 Therefore, China’s healthcare system is becoming increasingly hospital-centred, 14 15 which further worsens the quality of primary care and impedes the resilience of the whole healthcare system.…”
Section: Introductionmentioning
confidence: 99%